Advanced phase-lock techniques - Crawford, James A. (Artech House microwave library., 2007)
From cellphones to micrprocessors, to GPS navigation, phase-lock techniques are utilized in most all modern electronic devices. This high-level book takes a systems-level perspective, rather than circuit-level, which differentiates it from other books in the field.